Cultivation of Digital Literacy Based Communication in Natural Science Learning at Al-Abidin Primary School of Information and Communication Technologies - Putri Oviana; Sutama; Ahmad Muhibbin (Jurnal Penelitian Pendidikan IPA, 2024)
The aim of this research is to describe the cultivation of written-based aspects of communication digital literacy in learning Natural Sciences (Science) and exploring oral-based communication aspects digital literacy in learning Natural Sciences (IPA). The research method uses a qualitative research approach, the research design uses a case study. Data collection techniques in research are observation, interviews and document analysis. The results of the research show that communication culture is based on digital literacy and succeeded in creating a dynamic and innovative Natural Sciences (Science) learning environment. Students demonstrate significant improvement in the ability to use technology to express scientific ideas, both written and verbal. The use of digital tools such as Canva, PowerPoint and online collaboration platforms not only increases student engagement, but also facilitates a deeper understanding of Natural Sciences (Science) concepts. This culture successfully integrates aspects of written and oral communication, enabling students to develop the skills needed in the 21st century.